2016
DOI: 10.1111/ddi.12425
|View full text |Cite
|
Sign up to set email alerts
|

Use of marine protected areas and exclusive economic zones in the subtropical western North Atlantic Ocean by large highly mobile sharks

Abstract: The cover image, by Fiona Graham et al., is based on the Biodiversity Research Use of marine protected areas and exclusive economic zones in the subtropical western North Atlantic Ocean by large highly mobile sharks,: Metabarcoding reveals strong spatial structure and temporal turnover of zooplankton communities among marine and freshwater ports 493-504 D. Craven, E. Filotas, V. A. Angers and C. Messier: Evaluating resilience of tree communities in fragmented landscapes: linking functional response diversity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 69 publications
2
69
0
Order By: Relevance
“…The ECLSP has one of the densest populations of grouper in the Caribbean (Mumby et al 2011), likely as a result of the effective no-take reserve regulations. If conch predator populations are also thriving, including those of sharks and rays already benefiting from a Bahamian ban on harvest through some core portions of their range (Graham et al 2016), it may tip mortality rates to the point where few immature conch survive to maturity. A greatly increased mortality rate of juveniles and subadults would also likely result in a population slowly dying of old age.…”
Section: Discussionmentioning
confidence: 99%
“…The ECLSP has one of the densest populations of grouper in the Caribbean (Mumby et al 2011), likely as a result of the effective no-take reserve regulations. If conch predator populations are also thriving, including those of sharks and rays already benefiting from a Bahamian ban on harvest through some core portions of their range (Graham et al 2016), it may tip mortality rates to the point where few immature conch survive to maturity. A greatly increased mortality rate of juveniles and subadults would also likely result in a population slowly dying of old age.…”
Section: Discussionmentioning
confidence: 99%
“…Further, great hammerheads remained within relatively localized areas (e.g., Florida Keys and Daytona Beach) for extended periods of time, and made long-distance movements to and from predominant-use habitats. Graham et al (2016), using data from the same sharks with an additional six animals, found that 17.87% of their core habitat use areas were within the protected Florida state waters (5.6 km off shore in the Atlantic and 16.7 km offshore in the Gulf of Mexico), which prohibit the harvest, possession, sale and exchange of great hammerheads (Florida Fish and Wildlife Conservation Commission, 2011).…”
Section: Conservation and Management Implicationsmentioning
confidence: 99%
“…found their core habitat-use areas to be in the combined waters of Florida and U.S. exclusive economic zone (EEZ) (Graham et al, 2016). Documented movements into fronts within the Atlantic Ocean were further highlighted by Queiroz et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…It seems thus unlikely that the shark had moved at superficial waters from the oceanic province for such a protracted period, as proposed by the location estimates of the UKFSST algorithm. Considering that C. leucas exhibit a clear preference for coastal habitats (Carlson et al, 2010;Hammerschlag et al, 2012;Heupel et al, 2015;Graham et al, 2016), the fact that the maximum depth registered by the transmitter (64 ± 4 m) matches the minimum depth of the continental shelf break (Martins, Coutinho, 1981) suggests that this shark moved mostly within the neritic province. Previous tracking studies on C. leucas across the oceanic realm reported movements through greater depths (122-164 m) and lower temperatures (16-21ºC) (Carlson et al, 2010;Lea et al, 2015) than the shark tracked in this study, which sustain such a hypothesis.…”
Section: Discussionmentioning
confidence: 94%
“…Even though there is no evidence that this species copulates in freshwater, parturition likely occurs in warm-water estuaries and rivers (Montoya, Thorson, 1982;Compagno et al, 2005;Pillans et al, 2006). Adult C. leucas sharks make use of shallow nearshore habitats (Brunnschweiler et al, 2010;Hammerschlag et al, 2012;Heupel et al, 2015;Graham et al, 2016), particularly in areas of high freshwater inflow, associated with an elevated productivity, where they usually exhibit some level of site fidelity (Carlson et al, 2010;Daly et al, 2014). Nevertheless, this species also undertakes coastal migrations regulated by environmental, foraging and reproductive drivers (Daly et al, 2014;Espinoza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%